1984
DOI: 10.1044/jshd.4903.287
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Iconicity in Early Sign Language Acquisition

Abstract: A longitudinal study of sign language acquisition was conducted with 13 very young children (median age 10 months at outset of study) of deaf parents. The children's sign language lexicons were examined for their percentages of iconic signs at two early stages of vocabulary development. Iconic signs are those that clearly resemble the action, object, or characteristic they represent. Analysis of the subjects' vocabularies revealed that iconic signs comprised 30.8% of the first 10 signs they acquired. At age 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 0 publications
1
66
1
2
Order By: Relevance
“…The greatest degree of correlation was between AoA and iconicity (r .463, p .01); early acquired signs tended to be rated the most iconic. This trend may seem to contradict claims from research in ASL that iconic signs are not overly represented in children's earliest signs (Orlansky & Bonvillian, 1984) and that children's errors in producing iconic signs are not more iconic than the adult form (Meier, Mauk, Cheek, & Moreland, 2008). However, Orlansky and Bonvillian's claim was made only on the basis of parental reports from a limited number of observers, and even if this is true, a correlation between iconicity and AoA does not strictly imply that the earliest acquired signs will be noticeably more iconic.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…The greatest degree of correlation was between AoA and iconicity (r .463, p .01); early acquired signs tended to be rated the most iconic. This trend may seem to contradict claims from research in ASL that iconic signs are not overly represented in children's earliest signs (Orlansky & Bonvillian, 1984) and that children's errors in producing iconic signs are not more iconic than the adult form (Meier, Mauk, Cheek, & Moreland, 2008). However, Orlansky and Bonvillian's claim was made only on the basis of parental reports from a limited number of observers, and even if this is true, a correlation between iconicity and AoA does not strictly imply that the earliest acquired signs will be noticeably more iconic.…”
Section: Resultscontrasting
confidence: 45%
“…In our data, 17 of the 20 signs rated as earliest acquired were also iconic (i.e., had iconicity ratings above 4.0). However, we did not attempt to select the signs that are likely to be the very first acquired by children learning BSL from infancy, so this does not provide strong evidence against the findings of Orlansky and Bonvillian (1984).…”
Section: Resultsmentioning
confidence: 99%
“…With regards to language development, Orlansky & Bonvillian [36] reported no difference in acquisition between iconic and non-iconic signs by native signers learning American Sign Language (ASL) as their first language. However, this study did not control for other variables that might affect age of acquisition (such as familiarity and motoric/phonological complexity) and questions have been raised about their criteria for considering signs as being iconic [37].…”
Section: Language Studies: the Current Focus Approaches And Assumptionsmentioning
confidence: 99%
“…The first studies investigating sign language acquisition do not report a facilitating effect of iconicity. Based on parental reports, Orlansky and Bonvillian (1984) followed the linguistic development of 11 deaf children acquiring ASL from birth (age range: 0;04-1;02) and found that they produced an equal proportion of iconic and arbitrary signs. Meier, Mauk, Cheek and Moreland (2008) investigated if four deaf children acquiring ASL (age range: 0;08-0;17) had access to sign iconicity by assessing whether they enhanced signs' iconic features during spontaneous interactions with their caregivers.…”
Section: The Role Of Iconicity In the Acquisition Of Signed And Spokementioning
confidence: 99%
“…Iconicity also influences caregivers' communication in that it shapes the form of child-directed communication compared to adult-adult interactions (Akita, 2009;Yoshida, 2012). Regarding sign languages, traditional accounts concluded that iconicity does not play a role in sign acquisition (Meier, Mauk, Cheek, & Moreland, 2008;Newport & Meier, 1985;Orlansky & Bonvillian, 1984). However, more recent studies show that the first signs acquired by deaf children are iconic in nature (Thompson, Vinson, Woll, & Vigliocco, 2013).…”
Section: Introductionmentioning
confidence: 99%